Metallic Glasses - Minić, Dragica; Vasić, Milica (IntechOpen, 2020)
The term "metallic glasses" is widely used to denote the amorphous alloys obtained by rapid quenching techniques. These materials are characterized by short range atom ordering without translational periodicity of the structure. Kinetic and thermodynamic metastability is one of the main characteristics generally related to metallic glasses, while their thermally induced microstructural transformations could result in deterioration or improvement of the functional properties. Due to their favorable magnetic, electrical, mechanical, and anti-corrosion properties, metallic glasses as new and attractive materials have found application in many areas of modern industries - electronics, construction industry, aerospace industry; as well as chemistry, biomedicine, and surgery.